The Imprinted H19 LncRNA Antagonizes Let-7 MicroRNAs - Kallen, Amanda N. (2013)
Abundantly expressed in fetal tissues and adult muscle, the developmentally regulated H19 long noncoding RNA (lncRNA) has been implicated in human genetic disorders and cancer. However, how H19 acts to regulate gene function has remained enigmatic, despite the recent implication of its encoded miR675 in limiting placental growth. We noted that vertebrate H19 harbors both canonical and noncanonical binding sites for the let-7 family of microRNAs, which plays important roles in development, cancer, and metabolism. Using H19 knockdown and overexpression, combined with in vivo crosslinking and genome-wide transcriptome analysis, we demonstrate that H19 modulates let-7 availability by acting as a molecular sponge. The physiological significance of this interaction is highlighted in culture where H19 depletion causes precocious muscle differentiation, a phenotype recapitulated by let-7 overexpression. Our results reveal an unexpected mode of action of H19 and identify this lncRNA as an important regulator of the major let-7 family of microRNAs.